Three-dimensional unsteady radiative hybrid nanofluid flow through a porous space over a permeable shrinking surface - Wahid, Nur Syahirah (Physical Society of the Republic of China, 2023)
This study explores the heat transfer and fluid flow properties that occur within the radiative unsteady hybrid alumina-copper/water nanofluid flow through a porous space over a permeable shrinking surface in a three-dimensional domain. The fluid flow model in the form of partial differential equations is transformed into ordinary differential equations through dimensionless similarity variables. The finalized form of the model is then resolved using the finite difference method with the Lobato IIIa formula via the built-in MATLAB function known as bvp4c. Two nonunique solutions are executed; however, the second solution is not stable. The findings suggest that the effective heat transfer performance of the hybrid nanofluid can be established by increasing the porosity and suction parameters. The laminar flow phase can also be maintained by increasing the suction and porosity parameters while extensively shrinking the surface. However, a smaller magnitude of the shrinking capacity of the surface is suggested to result in a better heat transfer performance. Effective heat transfer can also be achieved by increasing the thermal radiation parameter within a specific range of smaller shrinking capacity. Overall, this study provides a vital guideline for simulating the fluid flow system and suggests strategies to optimize fluid flow and heat transfer performance.